Bibliometric analysis of acupuncture/acupressure publications used for the prevention/treatment of nausea and vomiting in children (Annals of Medical Research, 2023)
Aim: The aim of the present study is to analyze the literature on acupuncture/acupressure used in the prevention/treatment of nausea and vomiting in children and to guide future research.Materials and Methods: Between 01.01.1990 and 31.12.2022, publications on acupuncture/acupressure used for the prevention and treatment of nausea and vomiting in children were searched in the Web of Science Core Collection. The keywords used during this search were [''acupuncture OR acupressure'' (All Fields) and ''nausea OR vomiting' (All Fields) and ''pediatric OR paediatric OR child OR children'' (All Fields)]. The publications obtained after this search were scanned one by one and it was determined whether they were appropriate for the present study. The organizations, authors, countries, journals, publication languages and types, distribution of publications by years, Web of Science categories and the most used keywords in these studies were obtained from the Web of Science Core Collection. Descriptive analyzes were conducted in the light of the data obtained from the Web of Science Core Collection.Results: There are 117 publications on acupuncture/acupressure, which is used in the prevention/treatment of nausea and vomiting in children. 63.2% of all publications were published in the last 10 years. Of all publications, only 2 (French, German) were not in English. These 117 publications have been published in 64 different journals. The most active authors; Kelly KM (5 publications), Liodden I (5 publications), Norheim AJ (5 publications), Vohra S (5 publications), the most active country; USA, which has 46.1% of all publications, the most active journal; 40 (34.1%) ''Pediatrics'' and the most active organization; 8 (6.8%) “Harvard University”. The most frequently used keywords were “acupuncture, nause, vomiting, pediatrics and chemotherapy”. Looking at the distribution of publication types, almost 90% of all articles were research articles, 73 (62.3%) and reviews 32 (27.3%).Conclusion: All articles on acupuncture/acupressure used for the treatment/prevention of nausea and vomiting in the field of pediatrics published to date in the Web of Science Core Collection were analyzed in the present study. It is obvious that there is a large literature on this subject in pediatric patients, although it is not as extensive and comprehensive as in adults. Especially in the last 10 years, the number of publications has increased significantly, and it is possible to expect a wider range of literature on this subject in the coming years.
Keywords: Acupuncture; Acupressure; Child; Nausea; Vomiting